2021
DOI: 10.3389/fphar.2021.668952
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Initial Dose Regimen for Sirolimus in Pediatric Patients With Lymphangioma

Abstract: Sirolimus is an effective oral treatment for pediatric patients with lymphangioma. The present clinical study in 15 children (0.12–16.39 years of age) examines the effects of underlying factors on sirolimus concentrations through application of a population pharmacokinetic model. Using Monte Carlo simulation, an initial dose regimen for sirolimus in pediatric patients with lymphangioma is presented. It is found that the lower the body weight, the higher the clearance rate and sirolimus clearances are 0.31–0.17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
0
2
0
2
Order By: Relevance
“…Other co-medications, such as glucocorticoids, mycophenolic acid, and omeprazole, were not included in the final model as covariates. Many studies had demonstrated a nonlinear relationship between drug clearance and body weight in pediatric patients, and it may be well-represented by allometric scaling using a coefficient of 0.75 for clearance and a coefficient of 1 for volume ( Anderson and Holford, 2008 , 2011 ; Chen et al, 2021 ). In addition, a one-compartment model was used to describe tacrolimus in the present study as all the tacrolimus concentrations evaluated were trough concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Other co-medications, such as glucocorticoids, mycophenolic acid, and omeprazole, were not included in the final model as covariates. Many studies had demonstrated a nonlinear relationship between drug clearance and body weight in pediatric patients, and it may be well-represented by allometric scaling using a coefficient of 0.75 for clearance and a coefficient of 1 for volume ( Anderson and Holford, 2008 , 2011 ; Chen et al, 2021 ). In addition, a one-compartment model was used to describe tacrolimus in the present study as all the tacrolimus concentrations evaluated were trough concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Мы впервые в нашей стране в периоде новорождённости применили иммуносупрессивную терапию сиролимусом при врождённом пороке развития лимфатической системы согласно клиническим рекомендациям [12][13][14]. Результаты успешного лечения врождённого ХП и хилоторакса сиролимусом в литературе описаны достаточно широко [19][20][21][22].…”
Section: Discussionunclassified
“…Мама ребёнка была информирована и подписала добровольное письменное согласие на введение препарата. Назначение препарата сиролимус было принято согласно клиническим рекомендациям, а также рекомендациям Международного общества по изучению сосудистых мальформаций и данным современных публикаций [12][13][14].…”
Section: описание клинического случаяunclassified
“…In tuberous sclerosis complex patients, the sirolimus range was 5–15 ng/ml ( Wang et al, 2020 ). In pediatric patients with lymphangioma, the sirolimus range was also 5–15 ng/ml ( Chen et al, 2021a ). We simulated two different situations based on whether the children were co-administered posaconazole or not.…”
Section: Discussionmentioning
confidence: 99%